The speech of the companions of Imam Hussein (peace be upon him) in the Karbala incident: a persuasive approach (Journal of the College of Basic Education, 2024)
Discourse, any discourse, produces an intellectual interaction that influences and is influenced in a process that includes the elements of the transmitter and the receiver. Discourse, especially among groups, relies on persuasion as a dangerous mechanism for influencing the receiver and the possibility of changing his ideas, beliefs and perceptions, wherever they may be. Since the Karbala incident revolved around the paths of truth and falsehood, religion and disbelief, reform and corruption, persuasion was an important essence in the broadcasting process that Imam Hussein (peace be upon him) and his companions resorted to in order to cast an argument in the mind and heart of the other, and to try to dissuade him from his erroneous doctrinal, historical and religious perceptions. Various studies have been devoted to addressing Imam Hussein’s speech in the Karbala incident, and we decided to read the speech of his companions in the incident from a persuasive point of view, according to multiple strategies and images whose goal was to influence Yazid’s army. We briefly discussed the nature of discourse and its elements, the reality of persuasion in discourse, and then explained the most important persuasive strategies and their parts in those discourses, whether social, historical, or literary.